2007
DOI: 10.1002/art.22433
|View full text |Cite
|
Sign up to set email alerts
|

RANKL:Osteoprotegerin ratio and bone mineral density in children with untreated juvenile dermatomyositis

Abstract: Objective. To determine bone mineral density (BMD) in patients at the time of diagnosis of juvenile dermatomyositis (DM), to compare the RANKL: osteoprotegerin (OPG) ratio in patients with juvenile DM with that in healthy control subjects, and to evaluate whether BMD is associated with the RANKL:OPG ratio and the duration of untreated disease.Methods. Thirty-seven children with juvenile DM were enrolled. Dual x-ray absorptiometry (DXA) was performed before treatment, and Z scores for the lumbar spine (L1-L4) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…In contrast, osteoprotegerin (OPG), another receptor for TRAIL, inhibits TRAIL-induced apoptosis, due to the absence of a death domain [23]. In related studies, we found that sera from untreated patients with JDM contained a significantly lower level of OPG and patients with longer disease duration had an even lower serum OPG level [24], which may be associated with reduced inhibition of TRAIL-mediated apoptosis. However, the role of OPG in JDM requires further investigation.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, osteoprotegerin (OPG), another receptor for TRAIL, inhibits TRAIL-induced apoptosis, due to the absence of a death domain [23]. In related studies, we found that sera from untreated patients with JDM contained a significantly lower level of OPG and patients with longer disease duration had an even lower serum OPG level [24], which may be associated with reduced inhibition of TRAIL-mediated apoptosis. However, the role of OPG in JDM requires further investigation.…”
Section: Discussionmentioning
confidence: 87%
“…Even puberty does not seem to affect OPG concentrations, however the relatively small number of children that participated in our study make it difficult to draw a conclusion in this regard [16]. Controversial data exist in the literature regarding the association between OPG/RANKL system and BMD [6,7,[9][10][11][12]. Bucay N et al demonstrated a lower BMD and a higher incidence of fracture among OPGdeficient mice [8].…”
Section: Discussionmentioning
confidence: 91%
“…In this process, a RANKL-ligand present on the osteoblasts binds to RANK on osteoclast precursors to provoke their differentiation and inhibit osteoclast apoptosis [5,6]. Although OPG's mechanism of action has been described by in vitro and animal studies; human studies on OPG that investigated its association with BMD and other variables have yielded variable results and mostly failed to demonstrate a correlation between OPG and BMD [6][7][8][9][10][11][12]. Additionally, several studies on adults have suggested that OPG may have some effect on angiogenesis other than its association with vascular injury and atherosclerosis [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Our study stands unique for its timing of patient evaluation within 30 days of glucocorticoid initiation. The only other study conducted early in the course of the illness was by Rouster-Stevens et al (18), who assessed spine areal BMD by DXA in 37 children with untreated juvenile DM. They found that 6 (18%) of 33 evaluable patients had L-spine areal BMD Z scores less than Ϫ1.5, and that the L-spine BMD Z score was related to disease duration.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in lumbar spine (L-spine), femoral neck, and distal radial bone mineral density (BMD) in children with juvenile idiopathic arthritis (JIA) have been consistently documented among those who have been treated with glucocorticoids (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) and those who have not (1-6,8,9,12,14 -16). Reduced Lspine BMD has also been shown in children with juvenile dermatomyositis (DM) (17)(18)(19)(20)(21) and in juvenile systemic lupus erythematosus (SLE) (3,(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%